Allergy and autoimmunity in children: non-mutually exclusive diseases. A narrative review - D’Auria, Enza; Minutoli, Martina; Colombo, Alessandra; Sartorio, Marco Ugo Andrea; Zunica, Fiammetta; Zuccotti, Gianvincenzo; Lougaris, Vassilios (Frontiers in Pediatrics, 2023)
In last decades a simultaneous increase in the prevalence of atopic and autoimmune disorders in pediatric population has been observed. Despite the Th1-Th2 paradigm, supporting the polarization of the immune system with Th1 response involved in autoimmune diseases and Th2 response leading to hypersensitivity reactions, recent evidence suggests a possible coexistence of common pathogenic pathways as result of shared immune dysregulation. Similar genes and other mechanisms such as epithelial barrier damage, gut microbiota dysbiosis and reduced number of T regs and IL-10 contribute to the onset of allergy and autoimmunity. IgA deficiency is also hypothesized to be the crosslink between celiac disease and allergy by lowering gut mucous membrane protection from antigens and allergens. The present narrative review aims to give an overview of the co-occurrence of allergic and autoimmune disorders (celiac disease, inflammatory bowel diseases, type 1 diabetes mellitus, thyroid disease, juvenile idiopathic arthritis) in pediatric population, based on the available evidence. We also highlighted the common pathogenic pathways that may underpin both. Our findings confirm that allergic and autoimmune diseases are commonly associated, and clinicians should therefore be aware of the possible coexistence of these conditions in order to ameliorate disease management and patient care. Particular attention should be paid to the association between atopic dermatitis or asthma and celiac disease or type 1 diabetes and vice versa, for therapeutic interventions. Further studies are needed to better clarify mechanisms involved in the pathogenesis and eventually identify new therapeutic strategies.